Association between cardiac rhythm conversion and neurological outcome among cardiac arrest patients with initial shockable rhythm: a nationwide prospective study in Japan. Issue 2 (14th October 2020) - Kandori, Kenji; Okada, Yohei; Okada, Asami; Nakajima, Satoshi; Okada, Nobunaga; Matsuyama, Tasuku; Kitamura, Tetsuhisa; Narumiya, Hiromichi; Iizuka, Ryoji
Abstract: Aims: Initial cardiac rhythm, particularly shockable rhythm, is a key factor in resuscitation for out-of-hospital cardiac arrest (OHCA) patients. The purpose of this study was to clarify the association between cardiac rhythm conversion and neurologic prognosis in OHCA patients with initial shockable rhythm at the scene. Methods and results: The study included adult patients with OHCA due to medical causes with pre-hospital initial shockable rhythm and who were still in cardiac arrest at hospital arrival. Multiple logistic regression analysis was conducted to identify the adjusted odds ratios (AORs) and 95% confidence interval (CI) of cardiac arrest rhythm at hospital arrival for 1-month favourable neurologic status and 1-month survival, adjusted for potential confounders. Of 34 754 patients in the 2014–2017 JAAM-OHCA Registry, 1880 were included in the final study analysis. The percentages of 1-month favourable neurologic status for shockable rhythm, pulseless electrical activity (PEA), and asystole at hospital arrival were 17.4% (137/789), 3.6% (18/507), and 1.5% (9/584), respectively. The AORs for 1-month favourable neurologic status comparing to OHCA patients who maintained shockable rhythm at hospital arrival were PEA, 0.19 (95% CI, 0.11–0.32) and asystole, 0.08 (95% CI, 0.04–0.16), respectively. Conclusion: Findings showed that the 1-month neurologic outcome in OHCA patients who converted to non-shockable rhythm at hospital arrival was very poor compared with patients who had sustained shockable rhythm. Also, patients with conversion to PEA had better neurologic prognosis than conversion to asystole.